Improved biocompatibility of polyethylenimine (PEI) as a gene carrier by conjugating urocanic acid: In vitro and in vivo - Ihm, Jong Eun; Krier, Irina; Lim, Jeong M.; Shim, Sujin; Han, Dong Keun; Hubbell, Jeffrey A. (POLYMER SOC KOREA, 2015)
Polyethylenimine (PEI) is a promising gene carrier among polymeric vectors because of its high transfection efficiency, buffering capacity, which is responsible for its escape from endosomes, facility of modification, reasonable price and wide range of molecular weight. However, toxicity of PEI is an important obstacle to overcome for using it as a gene carrier in gene therapy protocols. In our study, PEI (10 kDa) was modified with urocanic acid, which has an imidazole ring (PEIU). This modification of PEI played an important role by improving transfection efficiency and reducing toxicity. The PEIU was condensed with DNA in different nitrogen of polycation/phosphate of DNA (N/P) ratios starting from 1.25. The PEIU/DNA complexes formed smaller (60-80 versus 100-400 nm) and less dispersible particles than PEI/DNA complexes. Cell viability test showed that in all the transfection experiments PEIU was always found less toxic than the PEI on three different cell-lines, Cos-7, HeLa, and 293T. The PEIU demonstrated improved biocompatibility as compared to the PEI. The in vitro transfection experiments showed that the PEIU displayed similar or lower transfection efficiencies than the PEI in the absence of serum. In medium complemented with serum, the PEIU had higher transfection efficiencies than the PEI. In vivo transfection experiments were carried out with intravenous and subcutaneous injections into mice. Five different organs were taken and lysed for quantification of expressed GFP. The quantification of the fluorescence of these organs exhibited that the PEIU has better transfection efficiency in in vivo experiments compared to the PEI. This study generated a strong evidence indicating that PEIU can be considered as a promising versatile gene carrier because of its biocompatibility and good transfection efficiency.
Keywords: MOLECULAR-WEIGHT; TRANSFECTION EFFICIENCY; VIRAL VECTORS; DELIVERY; DESIGN; EXPRESSION; COMPLEXES; POLY(ETHYLENIMINE); CYTOTOXICITY; CULTURE